Understanding psychopathology in migrants: A mixed categorical-dimensional approach. (May 2014) - Braca, Mauro; Berardi, Domenico; Mencacci, Elisa; Murri, Martino Belvederi; Mimmi, Stefano; Allegri, Fabio; Mazzi, Fausto; Menchetti, Marco; Tarricone, Ilaria
Background: Literature on mental disorders in migrants is constantly increasing. Only a few studies describe psychopathological dimensions in migrants over their nosographic diagnoses; however, there is a growing literature about the greater utility of a categorical-dimensional approach, rather than a solely categorical approach, in the understanding of mental disorders. The aim of this paper is to describe the phenomenology of mental disorders in migrants referred to the Transcultural Psychiatric Team of Bologna (BoTPT), by analysing the psychopathological dimensions that underlie their clinical diagnoses. Methods: We recruited all migrants who attended the BoTPT between May 1999 and July 2009. The psychopathological assessment was conducted with the Association for Methodology and Documentation in Psychiatry (AMDP) and clinical diagnoses were formulated according to ICD-10. We proceeded through a two-step analysis: (1) comparing the prevalence rates of psychopathological symptoms across diagnoses; then (2) conducting a factor analysis to assess how those symptoms configure psychopathological dimensions and how these dimensions underlie clinical diagnoses. Results: As expected, we found significant associations between diagnoses and the prevalence of their core psychopathological symptoms. Factor analysis revealed a strong polymorphism of the psychopathological presentation of mental disorders and unexpectedly showed that in each diagnostic cluster, the first extracted factor was not composed of core symptoms. Conclusions: A mixed categorical-dimensional approach seems to improve the description of the psychopathology among migrants, as it adds relevant information regarding psychopathological dimensions useful to the understanding of the peculiar clinical expressivity of our patients.